EFFECT OF ALTERNATIVE RAW MATERIALS OVER CLINCKER QUALITY AND CO2 EMISSIONS - LEONID VASILIU; LILIANA LAZAR; LĂCRĂMIOARA RUSU; MARIA HARJA (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
In the cement industry, the actual challenges are the preservation of the raw materials and energy resources, as well as reduction of pollutant emissions. In this context, the cement producers demand studies to reduce of the production costs and atmospheric emissions. One way to achieve these objectives, is to use alternative fuels or by-product raw materials. Any reduction in the required energy has a beneficial influence both on the viability of the cement plant and on the environment. One of the approaches aimed at reducing thermal energy consumption is the partial substitution of traditional raw materials (limestone, clay, gypsum) with other alternative materials, with a melting effect, among which stand out byproducts of the steel industry such as furnace and steel slag. Another way for preservation of energy resources is using alternative fuels instead of traditional fuels like coal, petroleum coke or gas. The clinkering process and clinker quality can be influenced by any additions, in this study was determined these influences.